MOHAMMAD SJAFE’I DAN KONSEPSI PEMIKIRAN PENDIDIKAN RUANG PENDIDIK INS KAYUTANAM - Hera - Hastuti (Universitas Negeri Yogyakarta, 2020)
One important aspect for a nation that is struggling for its independence is education. This was realized by the founding fathers of the nation long before independence. In essence, the initial thought about education based on nationality emerged as an alternative to Dutch colonial education. It was Mohammad Sjafe'i (1893-1969) Ranah Minang's son who founded an alternative school on 31 October 1926 in the Kayutanam area, or better known as the INS Kayutanam Educator Room. Sjafe'i is the antithesis of the colonial education system formed by the Dutch. Even though this is a Dutch educational product, it does not agree with the Dutch education pattern. Sjafe'i through her INS brought education aimed at zendings arbeid, who sought forms of education that were in harmony with the Indonesian nation, and in accordance with the character of Indonesian children. Specifically this article discusses the conception of Sjafe'i's educational thought which was applied to the school he founded, INS Kayutanam Educator's Room.